Evaluation of methods for the measurement of antibody-dependent enhancement of dengue virus infection using different FcγRIIa expressing cell lines - Shweta Chelluboina; Darshan Kshirsagar; Gauri Panzade; Akhilesh Chandra Mishra; Vidya Arankalle; Shubham Shrivastava (PLoS ONE, 2025)
Background Pre-existing dengue antibodies could potentially exacerbate disease severity through antibody-dependent enhancement (ADE). Current serological assays focus on measuring neutralizing antibodies for vaccine evaluation, but don’t measure sub-neutralizing antibodies that enhance infection via Fcγ receptors. Consensus on a standardized system for measuring dengue virus ADE remains elusive. Methods In this study, we compared and evaluated ADE responses using two different methodologies in healthy blood donors (n = 12) and secondary dengue patients’ (n = 12) samples with pre-existing IgG antibodies to dengue virus (DENV). We performed an ADE-infection assay in FcγRIIa-expressing U937, K562, and Vero-CD32a cells. Foci-reduction neutralization test (FRNT) was performed simultaneously in Vero and Vero-CD32a cells, and reduction in neutralization titres was examined in Vero-CD32a cells. Results Out of 12 blood donors, all 9 anti-dengue IgG-positive donors demonstrated ADE through infection-enhancement assay against DENV-2 and DENV-4 serotypes in U937 and K562 cells, but not in Vero-CD32a cells. None of the anti-dengue IgG-negative donor samples exhibited ADE against DENV in all three cell lines. Fold-enhancement of DENV-2 infection was comparable in the two cell lines whereas, fold-enhancement of DENV-4 infection was significantly higher in K562 than in U937 cells. Comparable neutralizing antibody titres in Vero and Vero-CD32a cells against DENV-2 and DENV-4 serotypes suggest that donor samples did not exhibit any enhancing activity in Vero-CD32a cells. Comparable DENV-2 titres and significantly lower DENV-4 titres were obtained in Vero-CD32a than in Vero cells in secondary dengue patient samples, indicating that enhancing activity was influenced by DENV serotypes. Conclusion In summary, infection-enhancement assay using K562 cells was superior to U937 and Vero-CD32a cells in evaluating ADE. Samples with high neutralizing activity demonstrated very low levels of infection-enhancing activity in Vero-CD32a cells. Comparison of FRNT titres in Vero and Vero-CD32a cells is not suitable for detecting ADE. Our findings suggest that infection-enhancing activities are apparent at sub-neutralizing concentrations of dengue virus antibodies in all individuals exposed to dengue virus.